Application of a highly simulated and adaptable training system in the laparoscopic training course for surgical residents: Experience from a high-volume teaching hospital in China - Xueliang Zhou; Yanfei Shao; Chao Wu; Luyang Zhang; Jiayu Wang; Ruijun Pan; Jing Sun; Weiguo Hu (Heliyon, 2023)
Objective: To explore the effectiveness, feasibility, and training effect of a highly simulated and adaptable laparoscopic training system in the advanced integrated two-stage laparoscopic simulation training course for surgical residents. Methods: This study prospectively took the surgical residents who received the advanced integrated two-stage laparoscopic simulation training course in our hospital from December 2019 to December 2021 as the research objects. In the stage one course, the trainees are randomly distributed into the dry simulation system group and Darwin laparoscopic training system group. The subjective assessment results of the trainees from the two groups are collected by questionnaires, and the simulation assessment results of the two groups are evaluated in a unified, objective, and standardized assessment form. The pre-course and post-course questionnaires were used to evaluate the feasibility and effectiveness of the Darwin system in the stage two course. Results: A total of 62 trainees completed the stage one and stage two courses. In the stage one course, the trainees were randomly distributed into the dry simulation trainer group (N = 19) and the Darwin group (N = 43). The results of the subjective assessment questionnaire showed that compared with the dry simulator group, the students in the Darwin group had higher subjective scores (P < 0.05). The objective assessment results for the 3 modules of ''One Track Transfer'', ''One Tunnel Pass'' and ''High and Low Pillars'' in the Darwin group were significantly better than those in the dry simulator group (P < 0.05). The trainees who received the stage two course completed the questionnaires before and after the course. The results showed that compared with pre-course evaluation, ''basic theoretical knowledge of laparoscopy'', ''basic skills of laparoscopy'', ''laparoscopic suture technique'' and ''camera-holding technique'' were significantly improved after training (P < 0.05). Conclusion: The highly simulated and adaptable laparoscopic training system is effective and feasible in the advanced integrated two-stage laparoscopic simulation training course for surgical residents.